(untitled) (Revista do Tribunal Regional Federal da 3ª Região, 2026)
This article examines the use of digital interfaces in legal mediation. The objective is to assess the potential and limitations of technology in conflict resolution, taking into account the convenience these tools offer in terms of reducing time and costs. Methodologically, this is a qualitative and exploratory study based on a literature review and documentary analysis of the topic. The study briefly addresses the historical evolution of access to justice in Brazil, the emergence of mediation as an alternative method of conflict resolution, and the rise of digital interfaces, from the first computers to today’s devices. It is concluded that, in addition to facilitating interaction between humans and machines, digital interfaces go beyond the mere function of instrumental communication tools, establishing conditions that shape users’ perceptions of themselves and the world, producing meanings that affect communication processes. Therefore, it is essential to recognize the limits and potential of this scenario for the dynamics of legal mediation, so that the incorporation of digital interfaces is conducted with caution and well-targeted criteria to ensure the expansion of access to justice in an inclusive, democratic, and human-centered manner.